An ovine model of spinal cord injury. (4th May 2017) - Wilson, Saul; Abode-Iyamah, Kingsley O.; Miller, John W.; Reddy, Chandan G.; Safayi, Sina; Fredericks, Douglas C.; Jeffery, Nicholas D.; DeVries-Watson, Nicole A.; Shivapour, Sara K.; Viljoen, Stephanus; Dalm, Brian D.; Gibson-Corley, Katherine N.; et al.
Abstract : Objective : To develop a large animal model of spinal cord injury (SCI), for use in translational studies of spinal cord stimulation (SCS) in the treatment of spasticity. We seek to establish thresholds for the SCS parameters associated with reduction of post-SCI spasticity in the pelvic limbs, with implications for patients. Study Design : The weight-drop method was used to create a moderate SCI in adult sheep, leading to mild spasticity in the pelvic limbs. Electrodes for electromyography (EMG) and an epidural spinal cord stimulator were then implanted. Behavioral and electrophysiological data were taken during treadmill ambulation in six animals, and in one animal with and without SCS at 0.1, 0.3, 0.5, and 0.9 V. Setting : All surgical procedures were carried out at the University of Iowa. The gait measurements were made at Iowa State University. Material and Methods : Nine adult female sheep were used in these institutionally approved protocols. Six of them were trained in treadmill ambulation prior to SCI surgeries, and underwent gait analysis pre- and post-SCI. Stretch reflex and H-reflex measurements were also made in conscious animals. Results : Gait analysis revealed repeatable quantitative differences in 20% of the key kinematic parameters of the sheep, pre- and post-SCI. Hock joint angular velocity increased toward the normal pre-injury baseline in the animal with SCS at 0.9 V. Conclusion : The ovine model is workable as a large animal surrogate suitable for translational studies of novel SCS therapies aimed at relieving spasticity in patients with SCI.